Connecting young people with literature: An analysis of pedagogical practices and their impacts - Fim, Luciana Carvalho dos Reis (Seven Editora, 2024)
This study addresses the distancing of high school students from Literature and the effectiveness of current pedagogical practices in teaching this field. The justification for the research stems from the growing perception that Literature, often approached in a fragmented and academic way, cannot engage students as it should. The main objective is to analyze how pedagogical practices influence the formation of readers and to explore alternatives to improve the engagement of young people with literary texts. To achieve these objectives, the methodology adopted included a theoretical review of the contributions of scholars such as Calvino and Todorov, in addition to the analysis of prevalent pedagogical practices. The research examines how these practices impact students' perception of Literature and evaluates the effectiveness of different educational approaches. The results show that current pedagogical approaches often lead to students' disinterest, highlighting the need for a reformulation of teaching strategies. The research suggests that more interactive and contextualized methods can improve young people's engagement with Literature and enrich their cultural and critical formation. It is concluded that a review of pedagogical practices is essential to revitalize students' interest in Literature and strengthen their connection with cultural heritage. DOI:https://doi.org/10.56238/sevened2024.026-057